Grafting: A Technique to Modify Ion Accumulation in Horticultural Crops - Nawaz, Muhammad A.; Imtiaz, Muhammad; Kong, Qiusheng; Cheng, Fei; Ahmed, Waqar; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2016)
Grafting is a centuries-old technique used in plants to obtain economic benefits. Grafting increases nutrient uptake and utilization efficiency in a number of plant species, including fruits, vegetables, and ornamentals. Selected rootstocks of the same species or close relatives are utilized in grafting. Rootstocks absorb more water and ions than self-rooted plants and transport these water and ions to the aboveground scion. Ion uptake is regulated by a complex communication mechanism between the scion and rootstock. Sugars, hormones, and miRNAs function as long-distance signaling molecules and regulate ion uptake and ion homeostasis by affecting the activity of ion transporters. This review summarizes available information on the effect of rootstock on nutrient uptake and utilization and the mechanisms involved. Information on specific nutrient-efficient rootstocks for different crops of commercial importance is also provided. Several other important approaches, such as interstocking (during double grafting), inarching, use of plant-growth-promoting rhizobacteria, use of arbuscular mycorrhizal fungi, use of plant growth substances (e.g., auxin and melatonin), and use of genetically engineered rootstocks and scions (transgrafting), are highlighted; these approaches can be combined with grafting to enhance nutrient uptake and utilization in commercially important plant species. Whether the rootstock and scion affect each other’s soil microbiota and their effect on the nutrient absorption of rootstocks remain largely unknown. Similarly, the physiological and molecular bases of grafting, crease formation, and incompatibility are not fully identified and require investigation. Grafting in horticultural crops can help reveal the basic biology of grafting, the reasons for incompatibility, sensing, and signaling of nutrients, ion uptake and transport, and the mechanism of heavy metal accumulation and restriction in rootstocks. Ion transporter and miRNA-regulated nutrient studies have focused on model and non-grafted plants, and information on grafted plants is limited. Such information will improve the development of nutrient-efficient rootstocks.